Meta-analysis of the effects of third-wave behavioural interventions on disordered eating and body image concerns: implications for eating disorder prevention. Issue 1 (2nd January 2019) - Linardon, Jake; Gleeson, John; Yap, Keong; Murphy, Kylie; Brennan, Leah
ABSTRACT: Third-wave behavioural interventions are increasingly popular for treating and preventing mental health conditions. Recently, researchers have begun testing whether these interventions can effectively targeting eating disorder risk factors (disordered eating, body image concerns). This meta-analysis examined whether third-wave behavioural interventions (acceptance and commitment therapy; dialectical behaviour therapy; mindfulness-based interventions; compassion-focused therapy) show potential for being effective eating disorder prevention programs, by testing their effects on eating disorder risk factors in samples without an eating disorder. Twenty-four studies (13 randomized trials) were included. Most studies delivered selective prevention programs (i.e. participants who reported elevated risk factor). Third-wave interventions led to significant pre–post ( g = 0.59; 95% CI = 0.43, 0.75) and follow-up ( g = 0.83; 95% CI = 0.38, 1.28) improvements in disordered eating, and significant pre–post improvements in body image ( g = 0.35; 95% CI = 0.13, 0.56). DBT-based interventions were associated with the largest effects. Third-wave interventions were also significantly more efficacious than wait-lists ( g = 0.39; 95% CI = 0.09, 0.69) in reducing disordered eating, but did not differ to other interventions ( g = 0.25; 95% CI = –0.06, 0.57). Preliminary evidence suggests that third-wave interventions may have a beneficial effect in ameliorating eating disorder risk.